ANALISIS MODEL KETERWAKILAN POLITIK ANGGOTA DPD RI PROVINSI JAWA TENGAH PERIODE 2009-2014 (STUDI TENTANG FUNGSI, TUGAS DAN WEWENANGNYA SEBAGAI REPRESENTASI KEPENTINGAN DAERAH) - Ratih Mega Swari; Fitriyah .; Susilo Utomo (Journal of Politic and Government Studies, 2013)
DPD presence raising hopes that the interests of the communities in the area and the problems faced in the area can be raised and fought at the national level. With the DPD, the public policies at both the national and local levels, is no longer expected to be harmful and even siding with the regional interests and the interests of Folk. DPD is required to perform a balancing power (checks and balances) due to the characteristics of DPD as a representative body composed of independent members, regardless of party politics, and elected directly by the people in the region. Therefore, the Council is also required to carry the aspirations of the voters in his district.To realize the legitimation of DPD and can function effectively as a representative of the area then it is necessary to strengthen the formulation of laws governing Council at the central position, that the amended Constitution. While relating the functions and positions needed to be strengthened DPD substantial and profound changes that DPD understand, understand and be able to apply the functions, duties and power, so the Council in the future to run more effectively. Model of political representation which is run by members of the DPD becomes important to be analyzed in order to know what kind of model is compatible with the DPD of Central Java Province as the representation of regional interests.